2023
DOI: 10.1001/jamadermatol.2023.0035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plasmapheresis vs Immunoglobulin as First Treatment After Ineffective Systemic Corticosteroid Therapy for Patients With Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis

Abstract: ImportanceStevens-Johnson syndrome and toxic epidermal necrolysis (SJS/TEN) are severe cutaneous adverse reactions, and patients with SJS/TEN frequently require intensive care. However, there is limited evidence on the clinical outcomes of immunomodulating therapy, including plasmapheresis and intravenous immunoglobulin (IVIG) in patients with SJS/TEN.ObjectiveTo compare clinical outcomes of patients with SJS/TEN who were treated with plasmapheresis first vs IVIG first after ineffective systemic corticosteroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Similarly, the administration of tumor necrosis factor α as an adjunct therapy being equally effective in patients with SJS/TEN has also been reported, despite the small sample size of the report compared with studies on cyclosporine . However, our study did not consider these immunomodulating agents as covariates . The rationale behind this was that the effectiveness of these drugs was not widely known during the study period (especially in the early 2010s).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, the administration of tumor necrosis factor α as an adjunct therapy being equally effective in patients with SJS/TEN has also been reported, despite the small sample size of the report compared with studies on cyclosporine . However, our study did not consider these immunomodulating agents as covariates . The rationale behind this was that the effectiveness of these drugs was not widely known during the study period (especially in the early 2010s).…”
mentioning
confidence: 91%
“…2,3 However, our study did not consider these immunomodulating agents as covariates. 4 The rationale behind this was that the effectiveness of these drugs was not widely known during the study period (especially in the early 2010s). This was owing to insufficient evidence at that time, and consequently, these drugs have not been covered by Japanese medical insurance for SJS/TEN.…”
mentioning
confidence: 99%
“…To the Editor We recently read the work of Miyamoto and colleagues regarding the use of plasmapheresis vs intravenous immunoglobulin (IVIG) therapy as the initial treatment for Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). The authors conducted a trial to assess the benefits of these therapies, acknowledging the lack of guidelines for treating these rare disorders. The study noted that systemic steroids, plasmapheresis, and immunoglobulins were among the most used treatment options.…”
mentioning
confidence: 99%
“…Another study in the meta-analysis reported a decrease in mortality from a 2.75 SCORTEN-predicted mortality rate to no reported mortality . The study by Miyamoto and colleagues also mentioned the benefits of IVIG in terms of decreased length of stay and hospitalization costs. It is important to mention a meta-analysis by Chen et al that showed a significantly reduced mean hospital stay from 23.9 days to 17.3 days when using a 3- to 10-day course of cyclosporine compared with 3 to 7 days of high-dose IVIG therapy .…”
mentioning
confidence: 99%
See 1 more Smart Citation